PENGARUH MOTIVASI KERJA, KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN KOREA BEST BANK CABANG DENPASAR - Ni Komang Tri Nadya Suci; I Nengah Suardhika (Jurnal Bakti Saraswati (JBS), 2025)
Human resources (HR) are one of the most important aspects in a company because they are key elements that influence the performance and success of the organization. Performance refers to how well a person, group, or organization carries out tasks or achieves set goals. In an individual context, performance is often measured based on a person's ability to complete their work effectively and efficiently. This research aims to determine the influence of work motivation, compensation and career development on the performance of Best Bank Denpasar branch employees. The research method used is quantitative. This research was conducted at Korea Best Bank Denpasar branch. In this research, the objects of research are work motivation, compensation, career development and employee performance. The population and sample in this study were 38 employees at Korea Best Bank Denpasar branch. Data analysis techniques use Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Test, Coefficient of Determination, F Test and t Test. Based on the results of the analysis, this research shows that work motivation has a positive and significant effect on employee performance at Korea Best Bank Denpasar branch. Compensation has a positive and significant effect on employee performance at Korea Best Bank Denpasar branch. Career Development has a positive and significant effect on employee performance at Korea Best Bank Denpasar branch. Suggestions for further research are to expand the scope of research by including other variables that might influence employee performance, such as work environment, leadership, organizational culture, and individual factors such as job satisfaction or stress. Future research is also recommended to involve a larger sample.